2008
DOI: 10.1002/chem.200800371
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Mediated Radical Polymerization of Acrylonitrile: Kinetics Investigations and DFT Calculations

Abstract: The successful controlled homopolymerization of acrylonitrile (AN) by cobalt-mediated radical polymerization (CMRP) is reported for the first time. As a rule, initiation of the polymerization was carried out starting from a conventional azo-initiator (V-70) in the presence of bis(acetylacetonato)cobalt(II) ([Co(acac)(2)]) but also by using organocobalt(III) adducts. Molar concentration ratios of the reactants, the temperature, and the solvent were tuned, and the effect of these parameters on the course of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 48 publications
4
131
0
Order By: Relevance
“…[44] Therefore, calculations for the present study were only carried out with B3PW91*. The contribution of exact exchange is reduced in this functional, which therefore provides better estimates of bond energetics for processes involving first-row transition metals in which a spin-state change is involved.…”
Section: Experimental Study On the [Coa C H T U N G T R E N N U N G (mentioning
confidence: 99%
See 2 more Smart Citations
“…[44] Therefore, calculations for the present study were only carried out with B3PW91*. The contribution of exact exchange is reduced in this functional, which therefore provides better estimates of bond energetics for processes involving first-row transition metals in which a spin-state change is involved.…”
Section: Experimental Study On the [Coa C H T U N G T R E N N U N G (mentioning
confidence: 99%
“…Diblock copolymers of VAc with N-vinylpyrrolidone, [19] styrene, [20] and acrylonitrile [21,22] have also been obtained by using [CoA C H T U N G T R E N N U N G (acac) 2 ]. The fluorinated analogues [Co-A C H T U N G T R E N N U N G (acac-F 3 )] (2; acac-F 3 = 1,1,1-trifluoropenta-2,4-dionato) and [CoA C H T U N G T R E N N U N G (acac-F 6 ) 2 ] (3; acac-F 6 = 1,1,1,5,5,5-hexafluoropenta-2,4-dionato) were investigated by Matyjaszewski et al for VAc and related monomers.…”
Section: ]A C H T U N G T R E N N U N G (Pvac)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of vinyl esters and some vinyl amides, DFT modeling showed that an extra-stabilization of the CACo bond occurred via an intramolecular chelation of the cobalt atom with the carbonyl function of the last monomer unit and is responsible for the good control observed (Scheme 2) [51,64]. This intramolecular chelation is made possible by the flexible geometry of Co(acac) 2 [67,68] that is not possible for cobalt complexes bearing tetradentate ligands with a rigid square-pyramidal geometry (such as cobalt porphyrins) [55,69,70]. Co(acac) 2 is however less efficient for acrylates polymerization as the result of the low stability of the CACo bond of the dormant species [71].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was used to prepare well-defined block copolymers by sequential OMRP of monomers of different reactivity (Scheme 3, route B). For example, the addition of DMF or DMSO to PVAcACo(acac) 2 chains allowed to properly initiate the acrylonitrile polymerization with the formation of welldefined PVAc-b-PAN block copolymers, which is not possible without the addition of the coordinating solvent [68]. It is worth noting that in these above-mentioned cases, these neutral ligands do not substitute the original ones but further coordinate the metal center (Scheme 3, route B).…”
Section: Introductionmentioning
confidence: 99%